Purification and Characterization of Amyloglucosidase Enzyme from the Thermophilic Endomycopsis fibuligera Using Sago Starch as a Substrate - Ahyar Ahmad; Harningsih Karim (Indonesian Journal of Chemistry, 2016)
An investigation on purification and characterization of amyloglucosidase enzyme from Endomycopsis fibuligera by fermentation of sago starch has been carried out. This enzyme is inductive and can be produced by fermenting sago starch in a medium containing E. fibuligera. Crude enzyme was obtained by centrifuging the medium cultures containing E. fibuligera at 6,000 rpm for 20 min and then adding with 0.15 M acetate buffer (pH 5.0). Enzyme activity was determined using Somogyi-Nelson method by quantifying the released glucose from amyloglucosidase catalysis of starch (0.2%) as substrate. Prepurification process was conducted by ammonium sulphate fractionation and it showed that the ammonium sulphate fractionation with the degree of saturation of 40-60% produced a maximum activity of enzyme. Purification by DEAE-Cellulose and Sephadex G-75 column chromatography produced three and one fractions with purifity 17.4 and 22.5 times, respectively, compared to the crude extract enzyme. Characterization of this enzyme showed the optimum condition at pH 5.0 and 55 °C with 0.2% starch as substrate. The amyloglucosidase activities was strongly increased by addition of Co2+ and Mn2+ ions, whereas the activities were weakly decreased by addition of K+, Mg2+, and Fe3+ ions.